Robotic Exoskeleton for Young Adult Large-Lesion Stroke: A Case Report - Arisanti, Farida; Yunita Sari, Alfi; Sulistyo Wulandari, Maria Agustina; Larasati, Rinesa; Biben, Vitriana (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Large-lesion stroke in young adults often causes severe functional impairment, severely inhibiting people’s reintegration and long-term autonomy. In the subacute phase, severe motoric weakness, postural instability, and decreased aerobic capacity often inhibit effective walking rehabilitation. Objective: To evaluate the potential benefits of integrating a robotic dermoskeleton (KEEOGO) into the "Assist-as-Needed" (AAN) framework to achieve overground walking and cognitive motor integration. Method: A 34-year-old male with subacute ischemic stroke who presented with right hemiparesis (Brunnstrom Stage 2) and severe ambulation disturbance. The patient participated in a 4 week program consisting of robotic-assisted overground walking sessions. The AAN methodology provides adaptive support, responding with motoric effort directly to the patient. Results and Discussion: Post-intervention outcomes showed significant improvement. Walking endurance, as measured by the 6-Minute Walk Test, shows a marked improvement, rising from 96 m to 145 m, gait speed (10-Meter Walk Test) improved from 0.25 m/s to 0.46 m/s and cognitive function (MoCA-Ina) improved from 11 to 20. Conclusion: Robotic-assisted overground walking using an adaptive exoskeleton may be a safe and effective adjunctive modality for improving motor and cognitive outcomes in young patients with large-lesion stroke